2005
DOI: 10.1002/cne.20600
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide/cyclic guanosine monophosphate signaling in the central complex of the grasshopper brain inhibits singing behavior

Abstract: Grasshopper sound production, in the context of mate finding, courtship, and rivalry, is controlled by the central body complex in the protocerebrum. Stimulation of muscarinic acetylcholine receptors in the central complex has been demonstrated to stimulate specific singing in various grasshoppers including the species Chorthippus biguttulus. Sound production elicited by stimulation of muscarinic acetylcholine receptors in the central complex is inhibited by co-applications of various drugs activating the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 62 publications
(92 reference statements)
5
43
0
Order By: Relevance
“…Lesions of the central complex in crickets (Huber, 1960a,b) led to inhibition of walking and acoustic behavior, whereas lesions in cockroaches caused deficits in turning behavior (Ridgel et al, 2007). Electrical and pharmacological stimulation in grasshoppers affected sound production (Wenzel et al, 2005;Hoffmann et al, 2007). Structural central-complex mutants in Drosophila showed defects in walking speed, leg coordination, and directional control of walking and flight, including abnormal optomotor responses (Bausenwein et al, 1986;Strauss and Heisenberg, 1993;Ilius et al, 1994;Strauss, 2002).…”
mentioning
confidence: 98%
“…Lesions of the central complex in crickets (Huber, 1960a,b) led to inhibition of walking and acoustic behavior, whereas lesions in cockroaches caused deficits in turning behavior (Ridgel et al, 2007). Electrical and pharmacological stimulation in grasshoppers affected sound production (Wenzel et al, 2005;Hoffmann et al, 2007). Structural central-complex mutants in Drosophila showed defects in walking speed, leg coordination, and directional control of walking and flight, including abnormal optomotor responses (Bausenwein et al, 1986;Strauss and Heisenberg, 1993;Ilius et al, 1994;Strauss, 2002).…”
mentioning
confidence: 98%
“…Further involvement in visual information processing, e.g., for habituation and dishabituation of movement detectors, has been suggested by Elphick et al (1996) on the basis of anatomical observations. In the acoustic communication of grasshoppers, NO release in the central complex of the brain plays a vital role in suppressing stridulation behavior under unfavorable conditions (Wenzel et al, 2005;Weinrich et al, 2008). In the honeybee, the NO/cGMP system is involved in sensory integration (Müller and Hildebrandt, 1995) and habituation of the proboscis extension reflex via a protein kinase A pathway (Müller and Hildebrandt, 2002).…”
mentioning
confidence: 99%
“…Recent studies in the grasshopper Chorthippus biguttulus have shown NADPH-diaphorase staining in neurons, which supply the peripheral layer of the upper division of the central body. Furthermore, activation of the NO/cGMP pathway has been able to inhibit sound production provoked by stimulation of muscarinic receptors in the central complex (Wenzel et al 2005). T. infestans possesses a well-developed stridulatory organ (Di Luciano 1981), and sound production has been related to mating behavior (Manrique and Lazzari 1994).…”
Section: Distribution Of Nos-limentioning
confidence: 99%